Sentinels of environmental change: shifts in fish diversity through the lens of artisanal fishers - Marco Aurélio Alves Santos; Fernando Mayer Pelicice (Neotropical Ichthyology)
Abstract River regulation has caused significant shifts in fish diversity, with severe impacts on small-scale artisanal fisheries, which depend on fishing resources for income, employment and food security. This study investigated how artisanal fishers perceive changes in fish diversity in response to river regulation, considering four facets: (i) fish abundance, (ii) species records, (iii) capture patterns, and (iv) most valued fish. Between August and October 2018, we conducted systematic interviews with 30 artisanal fishers that operate in the area impounded by Lajeado Dam (middle Tocantins River). Fishers mentioned 60 common names of fish, totaling 51 independent ethnospecies. According to fishers, non-migratory fishes flourished in the reservoir, while migratory fishes declined. Fishers mentioned nine taxa that appeared in the impounded area, and 20 that disappeared, mainly large migratory catfishes. Fishery catches before river regulation were composed of large migratory characids and catfishes, while landings in the reservoir were composed of mid-sized non-migratory fish. Fishers also reported changes in the composition of the most valued fish. These results expand the evidence that artisanal fishers identify major shifts in fish diversity following river regulation, demonstrating that they can act as permanent sentinels of environmental change and degradation.